2021
DOI: 10.4041/kjod.2021.51.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Invisalign® aligners in the treatment of severe gingival recession: A case report

Abstract: In this report, we demonstrate the effectiveness of the Invisalign ® system in the treatment of severe gingival recession and bone dehiscence through torque, translation, and intrusion movements in a young woman. Cone-beam computed tomography was used to assess bone parameters and check the teeth during treatment. The root of the mandibular right central incisor, which was buccally positioned and exhibited bone dehiscence of 9.4 mm, was moved toward the center of the alveolar process by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“… 14 , 30 , 32 , 33 In the present study, we used tomographic images acquired with a 0.25 mm voxel size, which is in accordance with the literature. 5 , 8 , 11 , 14 , 18 , 25 - 28 , 34 - 36 However, smaller voxel sizes would ideally be more appropriate for interpreting the obtained bone results with greater reliability.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 30 , 32 , 33 In the present study, we used tomographic images acquired with a 0.25 mm voxel size, which is in accordance with the literature. 5 , 8 , 11 , 14 , 18 , 25 - 28 , 34 - 36 However, smaller voxel sizes would ideally be more appropriate for interpreting the obtained bone results with greater reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Antanavičienė et al reported about improvement of 58.7% recession cases, while 36% of the analyzed recessions were stable, and 5.3% demonstrated progression after performed orthodontic interventions [ 1 ]. The case report of de Figueiredo et al demonstrated significant gingival recession and bone dehiscence reduction after the usage of clear aligner system, which helped to move the tooth root into the proper position within the alveolus [ 6 ]. Analogical positive recession repair outcomes were also reported during orthodontic treatment of anterior cross-bite [ 7 ] and Class II (division 1) malocclusion [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case report, it was possible to provide prosthetic treatment without any orthodontic correction and change in patient's dentogingival appearance with the newly formed esthetic profile of crowns and bridges. Nevertheless, several previous studies demonstrated a positive effect of orthodontic correction on the gingival contour changes, while also on the optimization of occlusal relationship [5][6][7][8][9][10]. Considering available evidences, it was chosen to provide pre-prosthetic orthodontic treatment to improve complex treatment outcomes [5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the torque expression is still a challenge in the use of these appliances [15,46,47] and should also be considered as a part of the digital planning. The Invisalign ® system introduced the use of power ridges, which are pressure lines close to the gingival margin for increasing the contact pressure on the tooth surface, to control the movement of the tooth around its centre of resistance [16,48]. For the upper central and lateral incisors and canines, the results between dental inclination and palatal bone thickness were significantly negative in the middle and apical thirds, which reflects a reduction of bone tissue in these areas when inclination increases, and vice-versa.…”
Section: Scocate Acrn Et Almentioning
confidence: 99%